An Analysis of written feedback from teachers on the writing of students composition - Zainul Arifin (Language-Edu, 2020)
zainularief1982@gmail.com  ABSTRACT The aim of this analysis was to investigate the form of remedial guidance a teacher requires for the writing of students. Twelve students from ten levels of state higher secondary school were studied according to certain criteria. The study employed a qualitative approach. The data sources collected in this analysis included written corrective feedback from the instructor on the development of students in class, concentrating on three types of mistake: the subject-verb error, choice of words, and sentence form in the descriptive text of the students. Such results have been analyzed and used the corrective feedback theoretical frameworks (2009) of Ellis, which include: direct feedback, indirect corrective feedback and metalinguistic corrective feedback, by analysis and interpretation of the teacher's written corrective feedback. The results of the study show the type of corrective to correct the descriptive writing of students used by the state high school teacher. Specific revisions are the form of corrections mainly used by teachers when reviewing their students ' grammar mistakes.. The students could understand their errors by providing the right way of doing this with direct corrective feedback.Keywords: Corrective feedback, Writing Composition, Direct Corrective Feedback, Indirect Corrective Feedback, Metalinguistic Corrective Feedback